2019
DOI: 10.1021/acsomega.9b02229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of K+, Mg2+, Ca2+, Zn2+, La3+, Cr3+, Ce3+, Ce4+, and Mo5+ Doping on the Adsorption Performance and Optical Properties of Sodium Titanate Nanotubes

Abstract: Metal-doped titanate nanotubes (TNTs) were synthesized using a simple ion-exchange method. Cations with different valencies (Mg2+, Ca2+, Zn2+, K+, Cr3+, Ce3+, Ce4+, Mo5+, and La3+) were used to assess their effects on the adsorption performance and optical properties of the prepared nanotubes. All samples were characterized by X-ray powder diffraction (XRD), field-emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDXS), and elemental mapping, and the optical properties were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…These results showed that the semiconductor band gaps could be modified in the range of 2.02–2.8 eV. 19 Additionally, Tang et al reported a comparative study of Ti-NT doped with various metal cations (Cu 2+ , Co 2+ , Ni 2+ , Fe 2+ , and Mn 2+ ). Nevertheless, the band gap energy was only slightly modified from 3.43 (Ti-NT) to 3.18 eV (Fe–Ti-NT).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results showed that the semiconductor band gaps could be modified in the range of 2.02–2.8 eV. 19 Additionally, Tang et al reported a comparative study of Ti-NT doped with various metal cations (Cu 2+ , Co 2+ , Ni 2+ , Fe 2+ , and Mn 2+ ). Nevertheless, the band gap energy was only slightly modified from 3.43 (Ti-NT) to 3.18 eV (Fe–Ti-NT).…”
Section: Introductionmentioning
confidence: 98%
“…14,18 In this regard, the inuence of different metal cations on the Ti-NT optical properties has been studied previously. 9,[19][20][21][22] Lee and Zaki studied the inuence of cations with different valences (Mg 2+ , Ca 2+ , Zn 2+ , K + , Cr 3+ , Ce 3+ , Ce 4+ , Mo 5+ , and La 3+ ). These results showed that the semiconductor band gaps could be modied in the range of 2.02-2.8 eV.…”
Section: Introductionmentioning
confidence: 99%
“…This ion-exchange doping method is also applicable for modification of Na-TNTs by various metal cations with different valences (e.g., K + , Mg 2+ , Ca 2+ , Zn 2+ , La 3+ , Cr 3+ , Ce 3+ , Ce 4+ , and Mo 5+ ), and the narrowed band gaps of metal-TNTs (2.02–2.80 eV) will enhance their potential application as photocatalysts under visible or solar light irradiation. The nonmetal doped TNTs (e.g., N-doped TNTs) also exhibit a narrower band gap but better visible-light response, as new linkages such as Ti–O–N, Ti–N–O, and N–Ti–O are formed, resulting in the efficient charge transfer and promoted photocatalytic ability. ,,, …”
Section: Tnt-based Photocatalysts For Water Decontaminationmentioning
confidence: 99%
“…Summary on band gap structures of TNT-based photocatalysts (information is obtained from the literature; ,, ,,,,, photocatalysts with no CB and VB data reported are not listed here).…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…Copper sulfate heptahydrate, chromium acetate, nickel acetate, and zinc sulfate heptahydrate were mixed with Na-TNTs to produce Cu-TNTs, Cr-TNTs, Ni-TNTs, and Zn-TNTs, respectively. The simple sonochemical method used here is the main technique implemented for preparing doped samples, 17 where the mixtures were exposed to ultrasonication with a probe sonicator (20 kHz, pulsed mode with 9.9 s on and 3 s off) for 15 min. To remove unreacted sodium salts, the obtained samples were then washed several times with bidistilled water.…”
Section: Preparation Of Metal-doped Titanate Nanotubesmentioning
confidence: 99%